2012
DOI: 10.1055/s-0032-1326740
|View full text |Cite
|
Sign up to set email alerts
|

Indications of Microsurgery in Soft Tissue Sarcomas

Abstract: The microsurgical repair of sarcoma defects is a reliable option that, though not free of complications, is necessary in selected cases such as patients receiving neoadjuvant treatments and those with head and neck location and high-grade tumors. The procedure enables both adequate oncosurgical resection and function preservation. Our microsurgical sarcoma reconstruction data, based on an observation period of 12 years and presenting the results of 42 free tissue transfers in 41 patients, adds further evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…Several authors have reported that local or regional flaps are associated with higher complication rates and have inferior functional results compared to free flaps ( 7 , 47 ), which is also our own experience. Some authors found that free-flap reconstruction after soft tissue sarcoma excision at the upper extremity is associated with increased morbidity but better local control ( 48 ).…”
Section: Reconstructionsupporting
confidence: 80%
“…Several authors have reported that local or regional flaps are associated with higher complication rates and have inferior functional results compared to free flaps ( 7 , 47 ), which is also our own experience. Some authors found that free-flap reconstruction after soft tissue sarcoma excision at the upper extremity is associated with increased morbidity but better local control ( 48 ).…”
Section: Reconstructionsupporting
confidence: 80%
“…Nevertheless, complication rates between the reconstruction techniques were not significantly different between microsurgical free flaps, local/regional flaps or split skin grafts, but significantly higher compared to primary closure. It is known that microsurgical reconstruction after sarcoma surgery is reliable and safe [38,39], and many authors favor the use of microsurgical flaps over local options with regard to functional outcome and complication rates [6,27,38]. Complication rates themselves were in accordance with the literature [40].…”
Section: Discussionsupporting
confidence: 54%
“…Still, applying plastic surgical principles facilitates limb preservation with the restoration of function even in large tumors. Thus, the utilization of microsurgical reconstruction in sarcoma defects represents a reliable and safe option (25, 26), and is favorable over local options in regards of complication rates and functional outcome (26, 27). By following oncosurgical principles, our results with low amputation rates resembled data published elsewhere (6).…”
Section: Discussionmentioning
confidence: 99%